Flood vulnerability analysis of low-rise middle-class residential structures in Metro Manila - Garcia, Karen D.G
The main purpose of the study is to describe the vulnerability due to flooding of low-rise middle -class residential structures in Metro Manila. This is because of the fact that Metro Manila is frequently exposed to the said natural disaster. The vulnerability of the city would be measured by means of relating damage costs to floodwater stage of elements at risk found in a single structure that represents the study area. This single structure, usually referred to as the model, is produced by taking the average of the characteristics and components of a number of houses surveyed within the study area. Coping mechanisms of a number of respondents are considered in the assignment of damage costs per stage. Damage costs of structural components and building contents in each stage are taken in fraction of the total costs in structural components and building contents before relating the damage costs to their corresponding stages. Flood vulnerability curves could already be produces. These curves reflect the most vulnerable parts and elements of the model. Once vulnerability of the model to clear-water flooding is produced, effects of debris loads on the damages would be analyzed. This is done by relating the increases in the expected debris accumulation found in 50cm stage intervals to the increases in the damage costs for the same stage intervals. With this, flood vulnerability curves considering the debris effects for the model can be produced. The flood vulnerability analyses have come to the conclusion that building contents incur the higher damage costs compared to structural components, and that debris loads do not cause significant increases in damages from that of clear-water flooding.